Taxonomic status and nomenclature of Tanacetum clusii (Asteraceae, Asteroideae, Anthemideae), with comments on its distribution - Viktor O. Nachychko; Clemens Pachschwöll; Mihai Puşcaş; Ghizela Vonica; Gergely Király (PhytoKeys)
The paper provides nomenclatural and taxonomic accounts on Tanacetum clusii, a diploid species found in the Eastern Alps, the Carpathians, and the Dinarides, as well as comments on its current distribution. A careful examination of historic taxonomic literature showed that the combination T. clusii was first proposed by Kerner and predates a currently used much younger isonym by Soják (1871 vs. 1971). One specimen, a karyovoucher from WU, is designated here as an epitype for the illegitimate name Pyrethrum clusii, upon which Chrysanthemum clusii, the basionym of T. clusii, is based. This designation aims to avoid ambiguity in the taxonomic interpretation of its previously selected lectotype. Based on examining the original material, a voucher from SIB is designated as a lectotype of the synonymic name Chrysanthemum subcorymbosum, a basionym of Tanacetum corymbosum subsp. subcorymbosum. The last name is the only correct one in the rank of subspecies when T. clusii is alternatively treated as a separate subspecies within T. corymbosum s.l. In addition, one specimen from SAMU is designated here as a neotype of Pyrethrum corymbosum f. macrocephalum, a newly discovered heterotypic synonym of T. clusii. The analysis of the current species distribution showed that T. clusii is native to Switzerland (confirmed!), Italy, Austria, Slovenia, Croatia, Bosnia and Herzegovina, Hungary (confirmed!), Slovakia, Poland, Ukraine, and Romania. Although currently not accepted for Switzerland in literature, T. clusii could be confirmed for the Swiss canton of the Grisons. The same applies for Hungary where, apart from the Bükk Mts in literature, new localities from the Kőszeg and Mátra Mts are presented here. Additionally, the presence of T. clusii in Bulgaria, the Czech Republic, France, Greece, Montenegro and Turkey has not been confirmed and recorded mistakenly in different sources.